New Method of Injured Nerve Repair - Korsak, Alina; Likhodiievskyi, Volodymyr; Sokurenko, Liudmyla; Chaikovsky, Yuri (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Innovative surgical techniques form the basis of therapeutic approaches to address the negative consequences of nerve damage. This study evaluated the effectiveness of nerve trunk regeneration after the use of an electrosurgical instrument by looking at the patterns of morphological changes in the injured nerve and the structural elements of the segment motor center.Methodology The study was performed on male Wistar rats divided into four groups: group 1, control; group 2, rats with simulated sciatic nerve injury with epineural sutures; 3, rats subjected to an experimental surgical procedure using high-frequency electric welding technology; and 4, rats with simulated sciatic nerve injury without posttransection repair. To study changes in the peripheral stump of the transected nerves and L5 segments of the spinal cord, we used histologic, immunohistochemical, and morphometric methods.Results At week 12 after the surgery, there were more S-100+ Schwann cells, increased expression of neurofilaments (NFs), and glial fibrillary acidic protein in the peripheral stump in group 3 than in groups 2 and 4, which indicates enhanced neurotization and myelination. Group 3 animals demonstrated reduced expression of S-100 and NFs in the motor center of the spinal cord compared with group 2 that suggests less pronounced reactive changes caused by electric welding technology.Conclusions The study showed a novel surgical method using an electrosurgical instrument in a welding mode to stimulate regeneration of the injured nerve and to cause less prominent reactive changes in its segment motor center.
Keywords: peripheral nerve injury; segment motor center; spinal cord; live tissue welding; electrosurgery